Gagasan Human Security Dan Kebijakan Keamanan Nasional Indonesia - Fitrah, Elpeni (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2015)
AbstractThis paper discusses the application of human security concept in national security policy inIndonesia. Societal change towards democratization after reform and the ongoing security sectorreform process in Indonesia has impacted on the changing security paradigm from highly state centeredsecurity into the paradigms that are more concern to non-traditional issues such as humansecurity (people-centered security). Regardless of the pros and cons as well as the breadth of themeaning of the human security concept, the concept of human security is viewed in this paper as apoint of view (perspective) or the government guidelines for setting national security policy. Thispaper argues that Indonesia has put the idea of human security in its national security policy, butits implementation has not been so good. Individuals or human beings or citizens in the concept ofhuman security in Indonesia are defined as social beings who are bound with their community. Keywords: security, human security, National Security Act Draft, National Security Policy. AbstrakTulisan ini membahas penerapan konsep human security dalam kebijakan keamanan nasionalIndonesia. Perubahan sosial menuju demokratisasi setelah melewati era reformasi serta prosesreformasi sector keamanan yang tengah berlangsung di Indonesia berdampak pada berubahnyaparadigmn keamanan- dari konsep keamanan yang sangat terpusat pada keamanan Negara kedalam isu-isu yang lebih bersifat non-tradisional seperti human security (keamanan yang terpusatpada manusia). Terdapat banyak pro dan kontra serta pengertian yang luas dari konsep humansecurity, namun di tulisan ini human security akan dilihat sebagai perspektif atau acuan bagipemerintah untuk mengatur kebijakan mengenai keamanan nasional. Tulisan ini berargumenbahwa Indonesia telah meletakkan ide human security dalam kebijakan keamanan nasional, namunimplementasinya masih belum sempurna. Individu atau manusia atau warga negara dalam konsephuman security di Indonesia didefinisikan sebagai makhluk sosial yang terikat dengankomunitasnya. Kata-kata kunci: keamanan, human security, rancangan UU Keamanan Nasional, kebijakankeamanan nasional.